PENGEMBANGAN USAHA KECIL DAN MENENGAH DI DUSUN TRAYEMAN, PLERET, BANTUL MELALUI PENDAMPINGAN IZIN USAHA MIKRO & KECIL - Eka Sulistyaningsih; Satrio Aji Pambudi (LPPM IST AKPRIND Yogyakarta, 2018)
Small and medium enterprises (SMEs) have a vital role in development and economic growth, not only in developing countries like Indonesia, but also in developed countries. Villagers of Trayeman, Pleret village most of the livelihood as perpetrators of SMEs. But with no legality of business, the perpetrators of SMEs cannot develop their business. Business legality through licensing is very important for SMEs to be able to facilitate business actors to access capital in developing their business and compete with other business actors. Therefore, we conduct assistance to legalize efforts to develop SMEs of Trayeman residents. This mentoring process through three stages of business data collection, counseling and application of business permits to the District. Based on data collection, business people in Trayeman numbered 12 people with different kind of business. Counseling explains the importance of business legalization (business legalization benefits) and the process of legalization of business for SMEs. After following the counseling, all business actors (amounting to 12 people) are interested in applying for a business license. The perpetrators of SMEs collect the requirements and then request a letter from the village then submitted to the districs.